Algorithm of tactical preparation of a professional basketball team during the competitive period - Nahornyi , Dmytro; Mitova , Olena (Sportyvnyi Visnyk Prydniprovia, 2026)
Introduction. The article addresses the current state of the problem of improving the tactical preparation of professional basketball teams during the competitive period. The features of scouting and game-plan development used in modern basketball to increase the effectiveness of team actions are examined. The scientific and methodological literature lacks scientifically substantiated algorithms that describe step-by-step preparation of a professional basketball team for the next match; therefore, developing such an algorithm is a relevant research direction for modern basketball practice. The aim of the study is to scientifically substantiate an algorithm for the tactical preparation of a professional basketball team within the between-game microcycle of the competitive period as preparation for the next match, based on team strategy, training practices, and analysis of basketball games. Methods. The study was conducted on the basis of BC “Cherkaski Mavpy” during the 2024–2025 season. Methods included analysis of scientific and methodological literature, pedagogical observation, data generalization and systematization, and mathematical statistics. A total of 134 training sessions with an overall duration of 202.5 hours and 38 official competitive-period matches were analyzed. Opponent video analysis was carried out using FastModel Sports. Results. A single-cycle macrocycle structure of preparation for a Ukrainian Superleague basketball team was identified, with a 4-week preparatory period and a 7-month competitive period. A regular change in the ratio of training types was established when transitioning from the preparatory to the competitive period: a substantial increase in the share of tactical preparation due to a reduction in the volume of physical preparation, which corresponds to the task of achieving maximal sports results. An algorithm for tactical preparation integrating strategic planning and training practices was scientifically substantiated. Five stages of game-plan formation were defined: video analysis of 2–3 opponent games with categorization of 100–120 clips by defensive and offensive elements; analysis of statistical indicators; formation of a game strategy (game plan); familiarization of the team with the opponent’s style of play; differentiated breakdown of defensive, offensive, and individual opponent characteristics (“Defensive" scouting, “Individual” scouting, “Offensive” scouting); implementation of the game plan in the team’s training process. The role of scouting as the informational basis for strategic and tactical decision-making was substantiated. Conclusions. An algorithm for the team’s tactical preparation for matches during the competitive period was scientifically substantiated, integrating team strategy, training practices, and analysis of competitive performance based on modern trends in basketball tactics and the use of modern software (Fast Model Sports). The content and sequence of the stages of tactical preparation for a game were revealed: from opponent video analysis with categorization of game episodes by types of offense and defense to the development of a game plan that considers the strengths and weaknesses of the opposing team. The role of scouting as a system-forming element of tactical preparation was determined, providing the informational basis for strategic and tactical decisions by the coaching staff.